PEMBENAHAN PERMUKIMAN PADAT DAN KUMUH DENGAN MENERAPKAN KONSEP LABIRIN YANG BERSENI THE LACI (THE LABIRYNTH OF ART AT CITY) - Risyalaina, Kania Ariyani; Cradia, Gia Ulfa; Hadi, Rochmat (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Slums is a residential area with a shape that is not structured, not patterned (eg location of the house and the way irregular, unavailability of public facilities, infrastructure and clean water facilities, toilets) physical form is not feasible for example regularly flooded each year. The research method used is descriptive qualitative research method because it aims to reveal the facts, circumstances, phenomena, variables and circumstances are. Through literature review, the study interpret the state of slums in Cicadas and ends with a conclusion. Cicadas is one of the slums in the city of Bandung. Slums are caused by low socio-economic conditions that require them to build residential coincide and minimal public facilities. With the new problem arose the idea that The Labirynth of Art in order to fix Bandung Cicadas region that includes dense residential category and this slum. The concept of the labyrinth is a concept that has artistic value, with dense settlement infrastructure that resembles the labyrinth and inside there are many works of art. The goal is simply to fix without having to displace or move and give a good visual impression for the houses that lined and crammed in along the way. With conditions already Cicadas shaped like a maze of twists and turns, just enough to fix the condition of the house. After it is applied the concept of artistic with painting the walls of the wall street. Painting made creative as possible so that there is appeal for people to see and admire. The paintings are also useful for children in infancy as a lesson, so that children in slums not minimal knowledge. In order for this concept goes well, hopefully all parties such as governments, consultants, artists, architecture and citizens involved further increase cooperation in the form of participating in order to settlements as expected.Keywords: Slums, area, labirynth, Cicadas Bandung